Understanding age and race disparities in the application of sentinel lymph node biopsy in breast cancer. Issue 8 (December 2016) - Radhakrishnan, Archana; Silverman, Paula; Pollack, Craig Evan; Pfoh, Elizabeth R; Shenk, Robert; Thompson, Cheryl L
Abstract : Sentinel lymph node biopsy (SLNB) is the standard of care for surgical evaluation of early-stage breast cancer and is being employed as a quality metric for accreditation of breast centers. Previous studies report disparities in SLNB receipt. The goal of this study is to determine SLNB rates and explore rationale for non-receipt of SLNB. Patients with early-stage breast cancer diagnosed between 2010 and 2011 were identified from the University Hospitals Case Medical Center tumor registry. Multivariable logistic models were used to identify clinical and demographic risk factors for patients who did not receive SLNB. We performed chart reviews to elucidate reasons for the lack of SLNB. Our total sample was 479 patients; of them 432 (90.2%) received SLNB. On average, patients who received SLNB were younger than those who did not receive SLNB (61 compared to 79 years, respectively). Patients ≥80 years were 96% less likely to receive SLNB compared to patients <65 years (OR 0.04; 95% CI 0.00 to 0.14). There were no differences in SLNB by race, between patients undergoing Medicare or Medicaid and managed care, by surgeon specialty, or across medical centers. Chart review determined that 45/47 patients did not have SLNB, because it was a clinical decision-making; advanced age (>80 years) was cited in 27/47 women. Older women had much lower odds of receiving SLNB; however, non-receipt of SLNB was often due to a clinical reasoning. Our study highlights the importance of clinical reasoning in receiving SLNB, whereas other studies solely employing administrative databases do not.